Identifying the Social Structure and the Inequality in Monetary Income of Russian Population - Bobkov, Vyacheslav Nikolaevich; Kolmakov, Igor Borisovich (Economy of Regions, 2017)
The article aims at identifying the social structure and the inequality in monetary income of the population in Russia. identification of the social groups with different levels of material well-being in a society with a high inequality in the distribution of living standard is a relevant topic. The integration of normative and statistical methods allows to consider the limitations of the existing model of the distribution of cash income and adjust the boundaries of social groups with different levels of material well-being. At the same time, we stay within the criteria for the social standards of the differentiation of living standards. The authors have corrected the specific weight of the Russian social groups with different levels of material well-being. To define these social groups, we have applied the system of normative consumer budgets for different level of material well-being. This paper discovers the intervals for the levels of income and consumption, which are not in contradiction with the normative approach and existing conditions of the Russian economic development. These intervals are advisable for the identification of the social groups with different levels of life. The proposed tools allow to integrate the measurements into the international system and define the place of Russia in terms of economic inequalities among other countries. The authors have assessed the weights of the different social groups, their share in the total volume of monetary income and their polarization in terms of living standards. The main conclusions of the article can be used as a theoretical, methodological and practical basis for identifying social structures in terms of living standards, determining their numbers and economic inequality. The research results can be introduced into the statistical monitoring of the living standards of the population.